Seroprevalence of hepatitis B in pregnant women in Mexico Seroprevalencia de hepatitis B en mujeres embarazadas en México - José Luis Vázquez-Martínez; María Ofelia Coreño-Juárez; Luis Felipe Montaño-Estrada; Michaël Attlan; Héctor Gómez-Dantés (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To determine the seroprevalence of hepatitis B in pregnant women from several regions of Mexico, as well as the risk factors associated with its occurrence. MATERIAL AND METHODS: A cross-sectional study was conducted between May and August 2000. It included 9 992 pregnant women attending the health services of the Mexican Institute of Social Security (Instituto Mexicano del Seguro Social-IMSS) in five cities: Tijuana, Ciudad Juarez, Acapulco, Cancun, and Mexico City (northeast and southeast regions). RESULTS: The overall prevalence for confirmed cases was 1.65% (165/9 992). The prevalences for individual cities were as follows: Tijuana, 1.27%; Ciudad Juarez, 1.46%; Acapulco, 2.47%; Cancun, 0.93%; northeastern Mexico City, 1.20%, and southeastern Mexico City, 2.52%. The risk factors found to be associated with HBsAg were: age, age at first sexual intercourse, city (Acapulco and southeastern Mexico City), and marital status (single or divorced). CONCLUSIONS: The prevalence of HBsAg in pregnant women (1.65%) was greater than that reported in previous studies and showed geographical differences. This high prevalence suggests that a considerable amount of cases of hepatitis B occurs perinatally and through contact with carriers in the general population. Vaccination of newborns of high-risk pregnant women should be considered. OBJETIVO: Determinar la seroprevalencia de hepatitis B en mujeres embarazadas de varias regiones de México e investigar factores de riesgo asociados. MATERIAL Y MÉTODOS: Durante el periodo de mayo-agosto del año 2000 se realizó un estudio transversal en 9 992 mujeres embarazadas, con acceso a seguridad social (Instituto Mexicano del Seguro Social) en cinco ciudades de México: Tijuana, Ciudad Juárez, Acapulco, Cancún y Distrito Federal (zona noreste y sureste). RESULTADOS: La prevalencia global para casos confirmados fue de 1.65% (165/9 992). Para las ciudades de estudio fue: 1.27% en Tijuana, 1.46% en Ciudad Juárez, 2.47% en Acapulco, 0.93% en Cancún, 1.2% en el noreste del Distrito Federal, y 2.52% en el sureste del Distrito Federal. Los factores de riesgo identificados fueron: edad, edad de inicio de vida sexual, ciudad (Acapulco y región sureste del Distrito Federal) y estado civil (solteras-divorciadas). CONCLUSIONES: La prevalencia de antígeno de superficie del virus de la hepatitis B (HBsAg, por sus siglas en inglés) en embarazadas (1.65%) es mayor a la reportada en investigaciones previas y muestra diferencias geográficas. Esta prevalencia elevada indica un número considerable de casos de hepatitis B ocasionados por vía perinatal y de portadores en nuestra población. Se debe considerar la vacunación en recién nacidos de mujeres embarazadas con alto riesgo.